Bioinspired Graphene Oxide Membranes with Dual Transport Mechanisms for Precise Molecular Separation. (9th October 2019) - Dou, Haozhen; Xu, Mi; Jiang, Bin; Wen, Guobin; Zhao, Lei; Wang, Baoyu; Yu, Aiping; Bai, Zhengyu; Sun, Yongli; Zhang, Luhong; Chen, Zhongwei; Jiang, Zhongyi
Abstract: The implementation of membrane technology to replace or combine with energy‐intensive cryogenic distillation for precise separation of ethylene/ethane mixture proves an extremely important yet highly challenging task. Inspired by the hierarchical structure and facilitated gas transport of biological membranes, a highly selective ethylene/ethane separation membrane is explored through the fixation of a silver ion carrier and the impregnation of ionic liquid within 2D nanochannels of graphene oxide laminate, where plenty of ethylene‐permeating in‐plane nano‐wrinkles and ethylene‐facilitated plane‐to‐plane nanochannels are constructed. By virtue of synergistic effects of molecular sieving and carrier‐facilitated transport, an unprecedented combination of high ethylene permeance (72.5 GPU) and superhigh ethylene/ethane selectivity (215) is achieved, out‐performing currently reported advanced membranes. Moreover, molecular dynamics simulations verify a favorable membrane nanostructure for fast and selective transport of ethylene molecules. This bioinspired approach with dual transport mechanisms may open novel avenues to the design of high‐performance membranes for precise molecular separation. Abstract : A bioinspired membrane with dual transport mechanisms of molecular sieving and carrier‐facilitated transport is designed by the fixation of a silver ion carrier and the impregnation of ionic liquid within 2D nanochannels of graphene oxide for precise molecular separation.